The effect of duodenogastric reflux on Helicobacter pylori presence and gastric histopathologic changes - Vildan TAŞKIN,; Murat SEDELE,; Osman SAKA,; Bülent KANTARÇEKEN, (Turkish Journal of Gastroenterology, 2019)
-